A Meta‐analysis of the Willingness to Pay for Cultural Services from Grasslands in Europe. (16th September 2019) - Huber, Robert; Finger, Robert
Abstract: We investigate the willingness to pay (WTP) for cultural ecosystem services from grasslands using a meta‐analysis based on 32 eligible research papers that provide in total 79 estimates. The average WTP (corrected for purchasing power) across these studies is 38 Euros per person per year. Yet, our analysis reveals that the transfer of these results needs careful evaluation. More specifically, it is essential to frame the monetary valuation exercise in relation to the direction of grassland change. A switch from cropland to grassland reduces WTP by 90 Euros while an increase in less‐intensive land‐use in mountain regions raises WTP by 53 Euros. We conclude that for an adequate consideration of grasslands in holistic ecosystem services assessments, the direction of grassland change is important.